1995
DOI: 10.1038/377162a0
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility to ultraviolet-induced carcinogenesis in mice lacking XPC

Abstract: Compromise of genetic information by mutation may result in the dysregulation of cellular growth control and subsequent tumour formation. Xeroderma pigmentosum (XP) is a rare autosomal disease characterized by hypersensitivity of the skin to sunlight and > 1,000-fold increased risk of skin cancers in sun-exposed parts of the body. Cell fusion studies have revealed eight complementation groups in XP (A-G, and an XP-variant form); group C is one of the most common forms of the disease. We have isolated a mouse h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
126
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(137 citation statements)
references
References 12 publications
7
126
1
3
Order By: Relevance
“…XP is characterized by extreme sensitivity to UV light, resulting in advanced degenerative changes on sun-exposed areas of the skin and eyes and a high predisposition to cancer. Deletion of NER genes in experimental animals that are then subjected to UV carcinogenesis protocols has corroborated these findings, demonstrating that NER is a primary defense against UV-induced cancer (de Vries et al, 1995;Nakane et al, 1995;Sands et al, 1995;Berg et al, 2000).…”
Section: Introductionsupporting
confidence: 54%
“…XP is characterized by extreme sensitivity to UV light, resulting in advanced degenerative changes on sun-exposed areas of the skin and eyes and a high predisposition to cancer. Deletion of NER genes in experimental animals that are then subjected to UV carcinogenesis protocols has corroborated these findings, demonstrating that NER is a primary defense against UV-induced cancer (de Vries et al, 1995;Nakane et al, 1995;Sands et al, 1995;Berg et al, 2000).…”
Section: Introductionsupporting
confidence: 54%
“…Deficiency in XPC has been implicated in tumorigenesis. For example, XPC-defective mice were highly prone to skin cancer following exposure to UV radiation [3] and also susceptible to common cancers such as lung, esophageal, and bladder cancers when exposed to chemical carcinogens [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mice harboring mutation in the XPA or XPC gene did not develop spontaneous tumors, however, they developed tumors at a high frequency upon UVB irradiation for a period of 20-30 weeks (Nakane et al, 1995;Sands et al, 1995). A recent study on DDB2À/À mice reported high incidences of UV-induced skin carcinogenesis (Itoh et al, 2004).…”
Section: Ddb2à/à Mice Are Susceptible To Uv-induced Skin Cancersmentioning
confidence: 99%